Decision-making in a changing climate: From analysis to guided adaptation action in cocoa, coffee and tea farming systems. - Schmidt, Paul; Kumari, Resham; Garcia, Rochelle; Juhrbrandt, Jana; Atienza, Lauro; Peñaflor, Zsarla; Bunn, Christian (2024)
This course equips you with the necessary knowledge and skills to effectively address the challenges posed by climate change in perennial tropical cropping systems such as cocoa, coffee, and tea. By enhancing your understanding of climate impacts and enabling you to utilize climate data within a comprehensive framework, this course aims to empower you to prioritize and implement adaptation strategies that can mitigate climate risks and foster resilience in cocoa, coffee, and tea production. Such capacity-building endeavors are vital for safeguarding the livelihoods of millions of farmers and ensuring the long-term sustainability of the respective industries.